Telaah Mudharabah At-Taawuniyah pada Asuransi BPJS Perspektif Ekonomi Syariah - Kholifatul Amanah; Lilik Rahmawati; Rajabiyah Khoirotin Ni’mah; Shakilla Husnia Al Fadhilah; Ully Amaliyah Butar Butar (Nurul Jadid University, 2020)
The Social Security Organizing Body or ordinary people used to call it BPJS is a state-owned legal entity whose job is to organize social security programs. When a social security program is managed by an institution, such as the BPJS, then the principle of al-takmin al-ta'awuni should be applied. And to implement these principles a Sharia Unit is needed. The purpose of this paper is to find out how BPJS is viewed in the perspective of Islamic Economics. The method used in this paper is a qualitative research method where the author uses field notes, interviews, and personal documents and other documents as a support in the results of this paper using descriptive data collection techniques that examine the data with the arrangement of words not with data number. Seen from the perspective of Islamic Economics, the contract on the manager of BPJS in Islamic economics can be known as mudharabah at-ta'awuniyah, which is a cooperation agreement to bear each other or risk each other with the principle of help-helping and mutual assistance. This has been included in one of the principles of Islamic Economics, namely mutual help.